The Impact of Static Fluid E-Module by Integrating STEM on Learning Outcomes of Students - Asrizal, Asrizal; Zan, Aprina Maharani; Mardian, Vivi; Festiyed, Festiyed (Journal of Education Technology, 2022)
Students' success in learning can be seen from the achievement of student competencies. This means that several factors affect student learning outcomes, such as learning materials or e-module. E-module is a module packaged in electronic or digital form that contains a variety of interactive media. The situation found in the field is that the teaching materials used are still in printed form or textbooks and student learning outcomes are still in the low category of students. This study aims to analyze the effectiveness of using STEM integrated e-module on static fluid materials. This research was quasi-experimental research with a single factor independent groups design. The research method used was the development method with the Hannafin and Peck instructional development model focused on product-oriented learning design. The instruments used in the study were final tests, observations, and worksheets. The data analysis techniques used in this research were descriptive statistical analysis, normality test, homogeneity test, t-test for two unrelated samples. Data analysis showed differences in learning outcomes in the experiment group compared to the control group. This indicates the influence of the STEM-integrated static fluid E-Module on student learning outcomes. Therefore, the STEM-integrated static fluid material electronic module design can improve student learning outcomes.